105 An intriguing case of pericardial effusion after acute coronary syndrome. (8th December 2021) - Giubertoni, Ailia; Rossi, Lidia; Cumitini, Luca; Airoldi, Luisa; Patti, Giuseppe
Abstract: Aims: Left ventricular free wall rupture is one of the mechanical complications of myocardial infarction with an incidence of 2–4%. Sometimes the myocardial rupture hasn't an immediate fatal evolution, nor is easy to be diagnosed because it is contained by the pericardium and thrombus formation, leading to pseudoaneurysm of the left ventricle. Pseudoaneurysms need a prompt surgical correction for their high risk of rupture both in the acute phase and later. Methods and results: A 57 years old, smoker, woman with no previous cardiological history was admitted to our cardiological department for acute coronary syndrome with persistent ST segment elevation involving the postero-lateral wall (door to balloon time about 10 h, Killip class I and peak hs-TnI value was 27.67 ng/ml n.v. ˂0.02 ng/ml). The echocardiography showed mild left ventricular disfunction (LV EF 45%), postero lateral akinesia and moderate mitral regurgitation; ubiquitous pericardial effusion (1 cm) was present, particularly along the anterior left ventricular wall, with irregular echo-dense aspect. She underwent urgent coronarography that showed a critical stenosis of the distal third of the left circumflex and a thrombotic occlusion of the first marginal branch. The distal circumflex was treated with angioplasty and stent implantation but we couldn't obtain the reperfusion of the marginal branch. Post procedural echocardiogram was unchanged and no free wall rupture was detected. 7 days after the admission, the patient showed persistent elevation of white blood count and CRP and developed fever, promptly empirically treated with a cephalosporin (blood cultures collected before were negative). After two new episode of fever with persisting biochemical flogistic parameters, a rheumatologic cause of the pericardial effusion was considered in the presence of positive antinuclear antibodies suggesting the diagnosis of Systemic Lupus Erythematosus. Steroidal therapy was prescribed which caused clinical improvement without complete resolution of the pericardial effusion. On day 20 of hospital stay a new echocardiographic evaluation showed a discontinuation of the postero lateral myocardial wall (Figure 1), about 1 cm in width, widely communicating with the left ventricular cavity and suggestive for a left postero-lateral ventricular pseudoaneurysm. The patient underwent surgical intervention and it was possible to expose a big clot occluding the pseudoaneurysmatic cavity communicating with the left ventricular chamber through an inlet about 1 cm in diameter, that was repaired with a bovine pericardial patch (Bard Sauvage technique). After surgery the patient was supported with an IABP and inotropes and was discharged to a rehabilitation structure on day 29 of hospital stay. Four months after the hospital discharge the patient died for a recently diagnosed pancreatic cancer. Conclusions: Pseudoaneurisms are life-threatening complications of myocardial infarction that sometimes are hardly diagnosed. When correctly recognized surgical correction can lead to a good prognosis.